SIMPLE FORMULA TO REPRESENT FLEXURAL CAPACITY OF PRESTRESSED CONCRETE - Youkhanna, Kanaan S. (European Scientific Journal, ESJ, 2014)
It is imperative for the structural designer to possess simple and reliable formulas to predict different aspects in structural behavior of reinforced concrete. Nowadays, mathematical formulas, as simple as possible, are required for computer aided design. This is a significant point to the present study. A theoretical review for the ACI Code analysis approach is presented. Theoretical formulae, based on the ACI Code ordinary approach, are derived to predict maximum and optimum prestressing steel. Theoretical simple formula is suggested to predict maximum flexural capacity for the prestressed concrete section. Theoretical factor R, that depends on fc ’ and fps, is presented to relate maximum to optimum prestressing steel. Another formula is derived based on the ACI Code ordinary approach to predict maximum flexural capacity for comparison with the suggested formula.